Historical Perspective And Future Projection Of Longwall Mining In The United States (19eaaffe-326c-46a4-9a81-dc104b2df560) - Thomas M. Barczak (International Conference on Ground Control in Mining, 1992)
This report chronicles the historical development of longwall mining in the United States and speculates on future developments to the turn of the century. Five eras of technological development during the modern period are described and analyzed. These eras discuss the development of (1) mechanized extraction, (2) self advancing roof supports, (3) high capacity roof supports, (4) shield supports, and (5) system automation. Current trends are analyzed in terms of: longwall utilization, production capability, support capacity, face widths, and new technological developments. From these analyses, the future of longwall mining to the year 2000 is speculated. It is concluded that longwall mining will continue to grow in importance during the next decade and that the next major technological milestone will be the realization of a fully automated longwall mining system.